On the unzipping mechanisms of carbon nanotubes: Insights from reactive molecular dynamics simulations - Dos Santos, Ricardo P. [UNESP]; Autreto, Pedro A.; Perim, Eric; Brunetto, Gustavo; Galvao, Douglas S. (Springer Nature, 2013)
Unzipping carbon nanotubes (CNTs) is considered one of the most promising approaches for the controlled and large-scale production of graphene nanoribbons (GNR). These structures are considered of great importance for the development of nanoelectronics because of its dimensions and intrinsic nonzero band gap value. Despite many years of investigations some details on the dynamics of the CNT fracture/unzipping processes remain unclear. In this work we have investigated some of these process through molecular dynamics simulations using reactive force fields (ReaxFF), as implemented in the Large-scale Atomic/Molecular Massively Parallel Simulator (LAMMPS) code. We considered multi-walled CNTs of different dimensions and chiralities and under induced mechanical stretching. Our preliminary results show that the unzipping mechanisms are highly dependent on CNT chirality. Well-defined and distinct fracture patterns were observed for the different chiralities. Armchair CNTs favor the creation of GNRs with well-defined armchair edges, while zigzag and chiral ones produce GNRs with less defined and defective edges. © 2012 Materials Research Society.
Keywords: Band-gap values; Defective edges; Fracture pattern; Graphene nanoribbons; Large-scale production; Mechanical stretching; Molecular dynamics simulations; Multi-walled; Parallel simulator; Reactive force field; Chirality; Enantiomers; Graphene; Multiwalled carbon nanotubes (MWCN); Molecular dynamics